The impact of a hearing-impaired child upon the parents : a comparative study of the stress experienced by the mother and by the father - Coetzer, Marie Anita (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1990.